2015
DOI: 10.5901/mjss.2015.v6n6s2p325
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Role of Project Management Office in the Success of Project-Based Organizations

Abstract: The present research investigates the role of project management office in project efficiency and thus its success. The statistical population used in this work includes construction corporations active in the Iran construction industry and familiar with the concept of project management office. In such organizations, existence of the project management office and the success of their projects is firstly assessed and the role of the project management office in success of the organization's project as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…There is also a specific reason why critical success factors are so important and should not be underestimated (overlooked). It turns out that a majority of construction projects fail to achieve the objectives of the schedule [35,36]. A significant number of construction project managers do not fully understand the critical success factors behind their projects, and, as a result, they prioritize non-essential tasks over those that really drive project progress [5].…”
Section: Introductionmentioning
confidence: 99%
“…There is also a specific reason why critical success factors are so important and should not be underestimated (overlooked). It turns out that a majority of construction projects fail to achieve the objectives of the schedule [35,36]. A significant number of construction project managers do not fully understand the critical success factors behind their projects, and, as a result, they prioritize non-essential tasks over those that really drive project progress [5].…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the management group was not fully cognisant of the full extent of the PMO which was discovered as a weakness in other research (Kiani et al, 2015;Dai and Wells, 2004). The most striking revelation was that strategic mandates identified in this study were omitted from the PMO's mandate, thus no concerted effort was made to ensure they are being pursued.…”
Section: Pmo Operations Inmentioning
confidence: 78%
“…Continuous PMO performance evaluation is vital to ensure that it is effectively satisfying stakeholders' needs, evolving to meet project delivery challenges and fulfilling organisational value (Kiani et al, 2015;Hill, 2004). Studies show that organisations' management are reluctant to support PMO efforts for reasons which include: its strategic value not being clearly understood (Dai and Wells, 2004), PMOs frequently failing to achieve their nominal mandates (Aubrey et al, 2013) and the PMO's dynamism being difficult to keep abreast with (Salamah and Alnaji, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the literature revealed the reasons behind the implementation of PMOs (Kutsch et al, 2015). In fact, the implementation of a PMO primarily contributes to improving project management maturity by enabling the acquisition of knowledge through lessons learned in previous projects and by providing a range of support and facilitation services for projects (Van der Linde & Steyn, 2016), but also plays a key role in the success of projects within organizations (Kiani et al, 2015). The study conducted by Babaeianpour and Zohrevandi (2014) showed that the implementation of the PMO has a significant effect on improving the project performance monitoring and control, crosscutting projects management and decision-making.…”
Section: Pmo Implementationmentioning
confidence: 99%